Charge Structure of Two Tropical Thunderstorms in Colombia. Issue 10 (22nd May 2019) - López, Jesús A.; Montanyà, Joan; van der Velde, Oscar A.; Pineda, Nicolau; Salvador, Albert; Romero, David; Aranguren, Daniel; Taborda, John
Abstract: Charge structure derived from lightning leader development of tropical thunderstorms comprising equatorial latitudes of less than ±10° has not been investigated yet. In this work, using a lightning mapping array installed in northern Colombia, the charge structure, lightning leader initiations, and the cloud‐to‐ground strokes rates of two thunderstorms have been analyzed. Additionally, radar information is also included. The identification of the charge regions has been obtained by analyzing the propagation of lightning leader developments. Flashes initiate between 4‐ and 15‐km altitude. High initiation rates are different in the two storms. In one case the high rates are found between 8 and 13 km. In the other case, the initiation heights are found between 10 and 15 km. The storms show typical tripolar charge structure where the upper positive charge is present at 10 to 15 km, the midlevel negative charge is found between 6 and 9 km, and the lower positive charge between 4 and 6 km altitude. Intracloud lightning flashes with inverted polarity have been identified for short period. In other periods, screening layer flashes have been detected at 14–15 km. The overall results show that the charge structures in the two Colombian storms are similar to the structures reported in North Central Florida, but with the significant difference that the flash initiation altitudes are 2 km higher in Colombia. The vertical configuration of the charge regions and the leader development of these thunderstorms may help explain the occurrence of terrestrial gamma‐ray flashes in tropical thunderstorms. Key Points: The investigated tropical thunderstorms reveal lightning leaders at high altitudes, with a maximum height of about 16 km Lightning initiates most frequently between altitudes from 6 to 14 km The analyzed Colombian tropical thunderstorms show a typical tripolar charge structure